Distinguishing features of immature stages of Panchaetothripinae (Thysanoptera: Thripidae) known in New Zealand. Issue 4 (1st October 2016) - Martin, NA
ABSTRACT: Diagnostic morphological characters of the juvenile Panchaetothripinae in New Zealand are illustrated. Keys developed enable colonies with only immature stages to be identified without needing to rear adults. Live larvae or larvae in ethanol are distinguished by the presence of expanded tips of body setae ( Parthenothrips dracaenae ), the absence of setae at the abdomen tip ( Hercinothrips bicinctus ), setae at abdomen tip not longer than abdominal tip width ( Heliothrips haemorrhoidalis ) and abdominal tip setae longer than abdominal tip width ( Sigmothrips aotearoana, endemic species). The presence or absence of spine-like setae on abdominal segments 9 and 10, and the number and length of setae on the wing buds, enable identification of pupae. Abdominal spine-like setae were on the prepupa and pupa of H. bicinctus and S. aotearoana, species that pupate off the plant, and are probably defensive structures. This is the first record of spine-like setae on segment 10 of terebrantian pupae.